Benefits of supplementation organically complexed trace minerals (Zn, Cu, Mn and Fe) in poultry and swine: A mini-review (Research, Society and Development, 2025)
The aim of this review is to provide a concise update on the benefits observed from supplementing organic trace minerals such as zinc, copper, manganese and iron in poultry and pig industry, with a focus on minerals complexed with non-specific amino acids and oligopeptides. A qualitative research of the narrative literature review type was conducted. Microminerals perform several essential functions in farm animals. Supplementation with microminerals in the form of complexed amino acids or small peptides can improve eggshell thickness and color in layer hens, prevent meat quality problems in broilers and maintain antioxidant capacity in pigs. In addition to improving production and health aspects, the use of organic minerals is associated with lower fecal excretion of these nutrients, which contributes to reducing negative environmental impacts, such as damage to plant growth, soil microbiota and ecological imbalance in general. It can be concluded that the use of organic minerals is a nutritional alternative with the potential to promote efficiency and reduce negative environmental impacts in the poultry and pig industry.